Perception of pain and discomfort during tooth separation - Nalbantgil Didem; Cakan Derya Germec; Oztoprak M. Oguz; Arun Tülin (Sciendo, 2023)
To evaluate patients' perceptions of pain and discomfort during tooth separation and to compare the effectiveness of brass wire and elastomeric separators.